El modelo social cognitivo en el desarrollo de las habilidades sociales en los niños de preparatoria de la EEB Bernardo Castillo de la parroquia de Quimiag en el periodo 2020 - 2021. - Déley, Ana Alexandra (2021)
This research was performed with children from "Bernardo Castillo" elementary school. The main objective was to strengthen social skills through the sociocognitive model, which considers the student not only as a subject who has the cognitive ability to build learning, but also as a producer of the multiple social interactions that he/she will carry out throughout his/her life. In "Bernardo Castillo" Elementary school, it was evidenced that the members of the educational community don’t have previous knowledge about the socio-cognitive model, its methodology and strategies in the teaching and learning process of children's social skills; therefore, the use of the methodological guide is proposed as a pedagogical tool in the educational process; it is important to give the necessary and adequate utility to each of the activities proposed in the research. The methodological design of the research is framed in the quantitative approach also called Positivist. In addition, with the help of the deductive method will evidence the two variables: cause and effect, which will allow us to statistically describe the facts. Through the application of various techniques such as: observation, interview, survey, to the subjects to investigate. The results of the application of the proposal in the valuation item “Acquired” we have an average 22,10%, before the application and 90,70% after the proposal. The importance of this research lies in the strengthening of social, socio-affective, and psychological skills, thus allowing an integral development in their learning process.